Pharmacotherapies Targeting GABA-Glutamate Neurotransmission for Treatment-Resistant Depression - Courtney M. Vecera; Alan C. Courtes; Gregory Jones; Jair C. Soares; Rodrigo Machado-Vieira (MDPI AG, 2023)
Treatment-resistant depression (TRD) is a term used to describe a particular type of major depressive disorder (MDD). There is no consensus about what defines TRD, with various studies describing between 1 and 4 failures of antidepressant therapies, with or without electroconvulsive therapy (ECT). That is why TRD is such a growing concern among clinicians and researchers, and it explains the necessity for investigating novel therapeutic targets beyond conventional monoamine pathways. An imbalance between two primary central nervous system (CNS) neurotransmitters, L-glutamate and γ-aminobutyric acid (GABA), has emerged as having a key role in the pathophysiology of TRD. In this review, we provide an evaluation and comprehensive review of investigational antidepressants targeting these two systems, accessing their levels of available evidence, mechanisms of action, and safety profiles. N-methyl-D-aspartate (NMDA) receptor antagonism has shown the most promise amongst the glutamatergic targets, with ketamine and esketamine (Spravato) robustly generating responses across trials. Two specific NMDA-glycine site modulators, D-cycloserine (DCS) and apimostinel, have also generated promising initial safety and efficacy profiles, warranting further investigation. Combination dextromethorphan-bupropion (AXS-05/Auvelity) displays a unique mechanism of action and demonstrated positive results in particular applicability in subpopulations with cognitive dysfunction. Currently, the most promising GABA modulators appear to be synthetic neurosteroid analogs with positive GABAA receptor modulation (such as brexanolone). Overall, advances in the last decade provide exciting perspectives for those who do not improve with conventional therapies. Of the compounds reviewed here, three are approved by the Food and Drug Administration (FDA): esketamine (Spravato) for TRD, Auvelity (dextromethorphan-bupropion) for major depressive disorder (MDD), and brexanolone (Zulresso) for post-partum depression (PPD). Notably, some concerns have arisen with esketamine and brexanolone, which will be detailed in this study.